The influence of nanosecond fibre laser on the removal of paint on metallic surface - R., Linggamm; M. Nasir, Bashir; Quazi, M. M.; M., Ishak (KKG Publications, 2021)
This research aims to study the effect of nanosecond laser parameters on the paint removal process and obtain a set of parameters that would result in the highest paint removal efficiency. In this study, the effect of laser paint removal parameters such as power, defocus distance, and the number of loops are studied with an optical microscope to observe surface features. The laser paint removal process is conducted using the IPG YLM 200/30 - Q pulsed fiber laser machine. The process sample was examined with an optical microscope to analyze the effectiveness of this laser paint removal process. The results indicated that the power and number of loops significantly enhance the paint removal process. The selection of correct frequency, power, hatching distance, scanning speed, and defocus distance also play a significant part in the efficiency of the laser paint removal process.